The Effect of Puzzle Games by Smart Phone in Vocabulary Mastery to the Student Junior High School - Hidayat, Khoirul; Habibi, Fajri (Attractive : Innovative Education Journal, 2024)
Nowadays content standard junior high school students are hoped to master vocabulary about 1000 words, so they can understand the conversation. But it fact, most of the students in junior high school do not master vocabulary well. So, the teacher should be able to choose a good media to help students to increase their vocabulary. In this case, Puzzle Games by Smart Phone is media that can be used to transfer vocabulary material for the students. The objective of this research is to find out the effect Puzzle Games by Smart Phone in vocabulary. This research was true experiment design. Pre test and post test were use to collect the data. There are two problems of the study, (1) is there any significant differences between before and after treatment in vocabulary mastery for the seventh grader students in SMP N 5 Sekampung Udik Satap in academic year 2023/2024?, (2) is there any effect of using Puzzle Games by Smart Phone in vocabulary student junior high school of SMP N 5 Sekampung Udik Satap in academic year 2023/2024?. As a source of data, the researcher utilized Puzzle Games by Smart Phone to teach vocabulary for the students. The media help students to learn vocabulary easier and more interesting to understand the subject, so their vocabulary would increase. The result of the research, it was found that the mean score of Puzzle Games by Smart Phone in pre test is 53,86, in treatment is 81, and in post test 85,33. It means that the student’s vocabulary has increased, and there is significant difference between before and after of using Puzzle Games by Smart Phone in vocabulary instruction. Keywords: Puzzle Games, Vocabulary Mastery, Smart Phone